Rekonstruksi Kewenangan Penyelesaian Perselisihan Hasil Pemilihan Umum - Harun, Refly (Jurnal Konstitusi, 2016)
Construction of authority in the settlement of dispute over the result of local election is still in transformation to become the ideal format. At the same time, the authority in the settlement of election dispute which is distributed to many agencies is also demanding simplification. The fact requires that there must be reconstruction on the settlement of all kinds of legal problems in election, including the dispute over local election results. Related to this, one of the proposals offered through this paper is the simplification of settlement system and the courts involved in the settlement of disputes. Where, for the settlement of disputed election results remain under the authority of the Constitutional Court, while the settlement of election disputes, local election disputes and disputes over the results of local election are handled by a special election court. The role of the election court referred to will be run by the Election Supervisory Body which will transform into a special election court.